Frozen Shoulder - Evaluating the Effectiveness of Physical Therapy against Other Interventions Like Corticosteroid Injections, Non-steroidal Anti-inflammatory Drugs (NSAIDs), and Surgical Options – A Literature Review - Michał Presak; Marlena Jankowska; Karolina Baran; Natalia Jańczyk; Karolina Mędrysa; Jakub Pokrzepa; Gabriela Blecharz; Julia Szwech; Alicja Winkowska; Adrianna Mielżyńska (Quality in Sport)
Frozen shoulder (adhesive capsulitis) is a prevalent musculoskeletal condition characterized by pain and progressive restriction of shoulder joint movement, significantly affecting quality of life. This literature review evaluates the comparative efficacy of physical therapy against other therapeutic interventions, including corticosteroid injections, NSAIDs, and surgical options such as manipulation under anesthesia and arthroscopic capsular release. The study highlights the need for individualized treatment strategies and further research to refine clinical guidelines.